Importancia de las sociedades cooperativas como medio para contribuir al desarrollo económico, social y medioambiental, de forma sostenible y responsable - Puentes Poyatos, Raquel; Velasco Gámez, María Del Mar (REVESCO. Revista de Estudios Cooperativos, 2009)
In recent years we have witnessed a major transformation of society, as a result of socio-economic changes that have influenced one hand, the emergence of new economic activities (new sources of employment) to cover the new needs of society without compromising those of future generations and, secondly, in the flowering of values in society which calls for a development economically, socially and environmentally sustainable and responsible.In this context, the objective of the article is to highlight the importance of cooperative societies as a way to contribute to sustainable development, to the extent that its activity is based on the use of endogenous resources of the area, by its nature economic - Social are appropriate for launching the activities of new sources of employment and work in a socially responsible way, according to cooperative principles and values.
Keywords: Cooperative Societies; New Sources of Employment; Corporate Social Responsibility and Sustainable Development